PERLUASAN KEWENANGAN MAHKAMAH KONSTITUSI DALAM MENANGANI CONSTITUTIONAL COMPLAINT PERSPEKTIF SIYASAH SYARIYYAH - Hamzah, Risnuansyah (SIYASATUNA : JURNAL ILMIAH MAHASISWA SIYASAH SYAR'IYYAH, 2024)
The rule of law that emphasizes that the constitution is the highest law of a country is known as the doctrine of constitutionalism.  The connection with the Constitutional Complaint is a legal effort for citizens to file complaints to the Constitutional Court with the argument of fighting for the constitutional rights of citizens so that they are not injured by arbitrary actions by the government.  This study aims to determine the urgency of expanding the authority of the Constitutional Court in dealing with Constitutional Complaints.  This type of research is normative legal research.  Sources of data in the form of primary and secondary data obtained through the analysis of various books, journals and laws and regulations that are correlated with the problems studied.  The results of the study indicate that the urgency of adding and expanding the authority of the Constitutional Court to examine and adjudicate Constitutional Complaint cases is very important for Indonesian citizens as an effort to protect citizens' constitutional rights which have been mandated by the 1945 Constitution and laws and regulations.  The idea of ​​Constitutional Complaint in the perspective of Siyasah Syariyyah upholds the rights of the community with the existence of a madzalim court institution which is used as a forum to obtain justice and legal certainty over acts of arbitrariness by the government at that time.